TOX4 and NOVA1 proteins are partners of the LEDGF PWWP domain and affect HIV-1 replication. - Mehdi Morchikh (Public Library of Science (PLoS), 2013)
PWWP domains are involved in the chromatin attachment of several proteins. They bind to both DNA and proteins and their interaction with specific histone methylation marks define them as a new class of histone code readers. The lens epithelium derived growth factor (LEDGF/p75) contains an N-terminal PWWP domain necessary for its interaction with chromatin but also a C-terminal domain which interacts with several proteins, such as lentiviral integrases. These two domains confer a chromatin-tethering function to LEDGF/p75 and in the case of lentiviral integrases, this tethering participates in the efficiency and site selectivity of integration. Although proteins interacting with LEDGF/p75 C-terminal domain have been extensively studied, no data exist about partners of its PWWP domain regulating its interaction with chromatin. In this study, we report the identification by yeast-two-hybrid of thirteen potential partners of the LEDGF PWWP domain. Five of these interactions were confirmed in mammalian cells, using both a protein complementation assay and co-immunoprecipitation approaches. Three of these partners interact with full length LEDGF/p75, they are specific for PWWP domains of the HDGF family and they require PWWP amino acids essential for the interaction with chromatin. Among them, the transcription activator TOX4 and the splicing cofactor NOVA1 were selected for a more extensive study. These two proteins or their PWWP interacting regions (PIR) colocalize with LEDGF/p75 in Hela cells and interact in vitro in the presence of DNA. Finally, single round VSV-G pseudotyped HIV-1 but not MLV infection is inhibited in cells overexpressing these two PIRs. The observed inhibition of infection can be attributed to a defect in the integration step. Our data suggest that a regulation of LEDGF interaction with chromatin by cellular partners of its PWWP domain could be involved in several processes linked to LEDGF tethering properties, such as lentiviral integration, DNA repair or transcriptional regulation.